Answer:
The following equation has:
Unique solution (one solution i.e. (4,1) )
Explanation:
The system of equation is given by:
y= -x + 5-----------(1)
and y= x - 3------------(2)
Now, on substituting the value of y from equation (1) into equation (2) we have:
![-x+5=x-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6ohajj78kveyi0nyz35a7lguoa5iadew2e.png)
On adding x on both the sides of the equation we have:
![5=x+x-3\\\\5=2x-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/we223t9rfn4fvjhrbxte5ty1gv3cdh9kep.png)
on adding 3 on both the sides of the equation we have:
![2x=5+3\\\\2x=8\\\\x=(8)/(2)\\\\x=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tans6o1155s2kqysjesq7kjzg3fshyb5qx.png)
Now, on putting the value of x into equation (2) we have:
![y=4-3\\\\y=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kbtr1fxz2f8sc87kxlqsxfkao0ivct3tkp.png)
Hence, the solution is unique (one solution )
Also, the point of intersection of the graph of two equations is solution to the system of equations.